An advanced biomass gasification technology with integrated catalytic hot gas cleaning. Part II: Tar reforming using char as a catalyst or as a catalyst support - Zhang, Shu; Asadullah, Mohammad; Dong, Li; Tay, Hui-Ling; Li, Chun-Zhu (Elsevier Ltd, 2013)
This paper aims to demonstrate the effectiveness of tar reforming in a pilot gasifier using char as a catalyst or as a catalyst support in our advanced biomass gasification system with integrated catalytic hot gas cleaning described in Part I. Biomass char, iron supported on biomass char and iron supported on brown coal char were used as hot gas cleaning catalysts at atmospheric pressure and 800 °C. The operation results in the lab-scale pilot plant show that all catalysts would decrease CO2 and CH4 concentrations and increase H2 and CO concentrations of product gas. The iron-containing species in char would favor the formation of H2. Tar contents below 100 mg/N m3 in the product gas could be obtained by using iron catalyst supported on biomass char or just biomass char. Most of larger aromatic ring systems in tar can be catalytically reformed by the iron-containing species. As for the effects of catalyst support, the iron catalyst supported on biomass char showed higher activities than that supported on brown coal char. The activity of catalyst for reforming tar was not directly proportional to the surface area and pore volume, while it was related to carbon structure in the char support.